EFEKTIVITAS KEPEMIMPINAN KEPALA MADRASAH SEBAGAI PENGAMBIL KEPUTUSAN (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2021)
Decision-making is one of the many problems a leader faces, especially when running an educational institution in Madrasah. The effectiveness of the madrasa director's leadership largely determines the future progress of the madrasa with various considerations that must be taken into account in order to find solutions to complex problems that arise in an institution he leads. Decision making is the most important part of planning activities. A decision made can have an impact on the solution of problems or, on the contrary, add new problems. This paper will analyze the effectiveness of the madrasa director's leadership as a manager in making good decisions that will affect the progress of the madrasa in the future.